Food aroma evolution : during food processing, cooking and aging - Bordiga, Matteo; Nollet, Leo M. L., 1948- (Boca Raton : CRC Press, 2019)
"Of the five senses, smell is the most direct and food aromas are the key drivers of our flavor experience. They are crucial for the synergy of food and drinks. Up to 80% of what we call taste is actually aroma. This book deals with how food aromas are developed and affected during food processing, cooking, and aging"--
OCLC-licensed vendor bibliographic record.
Keywords: Food -- Biotechnology; Food -- Odor; Food -- Sensory evaluation; Flavor; TECHNOLOGY / Food Science